The Chilean New Song Movement: Culture and Counterhegemony - Mcsherry, P (UNIV VALENCIA, DEPT PREHISTORIA & ARQUEOLOGIA, 2021)
This article analyzes the Chilean New Song movement (NCCh) as an integral component of a powerful counterhegemonic movement in Chile, formed in the mid-1960s, and key in the election of President Salvador Allende in 1910. The songs of the New Song movement not only denounced injustices but also articulated the dreams and hopes of multitudes of Chileans for a future of social justice and dignity. The musicians were simultaneously social communicators, historians, teachers, organizers, and interpreters of popular aspirations. They gave concerts in union halls from the north to the south of Chile, and in hundreds of student assemblies and meetings of campesinos in the rural areas. I use Antonio Gramsci s concepts to assess the significance of NCCh, particularly Gramsci s ideas about hegemony and the role of organic intellectuals. I interpret the role of the musicians as organic intellectuals as their music gave voice to the voiceless, visibilized their struggles, and made a new society of social justice in Chile seem possible and achievable.